Carrier-Based Common Mode Voltage Control Techniques in Three-Level Diode-Clamped Inverter. (19th September 2012) - Chaturvedi, Pradyumn; Jain, Shailendra; Agarwal, Pramod
Abstract : Switching converters are used in electric drive applications to produce variable voltage, variable frequency supply which generates harmful large dv / dt and high-frequency common mode voltages (CMV). Multilevel inverters generate lower CMV as compared to conventional two-level inverters. This paper presents simple carrier-based technique to control the common mode voltages in multilevel inverters using different structures of sine-triangle comparison method such as phase disposition (PD), phase opposition disposition (POD) by adding common mode voltage offset signal to actual reference voltage signal. This paper also presented the method to optimize the magnitude of this offset signal to reduce CMV and total harmonic distortion in inverter output voltage. The presented techniques give comparable performance as obtained in complex space vector-based control strategy, in terms of number of commutations, magnitude, and rate of change of CMV and harmonic profile of inverter output voltage. Simulation and experimental results presented confirm the effectiveness of the proposed techniques to control the common mode voltages.